Strengthening the HEI ecosystem in producing graduates oriented to entrepreneurial thinking and tend job opportunities - Irma Wani Othman; Anna Lynn Abu Bakar; Suwaibah Zakaria; Muhammad Safuan Yusoff (Academic Inspired Network, 2022)
Entrepreneurship development and education is an important agenda in ensuring that the country's higher education system is always competitive and moves forward according to current global demands and trends. The objective of this paper is to discuss the efforts and initiatives of various parties towards strengthening the ecosystem in producing Higher Education Institutions (HEI) graduates who have an entrepreneurial orientation, inclined towards careers as entrepreneurs and have the confidence to create job opportunities. This study uses a qualitative method which is a document analysis study or a library study where a survey of secondary sources whether online that refer to articles, books, papers, forums, and government policies related to the entrepreneurial ecosystem of HEIs is done. The results of the study examine a selection of contemporary issues that dominate the latest discussions regarding the entrepreneurial mindset among students. The issues highlighted are related to, 1. HEI Students' Competence as Entrepreneurs, 2. HEI Students' Exposure to the Business World, 3. HEI Students' Emphasis on Innovation and Technology in the Field of Entrepreneurship and 4. HEI Students' Emphasis on Entrepreneurship in Ensuring Sustainability Ecosystem in HEIs. The results of the study found that the manifestation of the entrepreneurship agenda at the university level can be measured through numerous key achievements such as the number and impact of student involvement in entrepreneurship activities and learning as well as the increase of academic staff who are competent and have expertise in the field of entrepreneurship education. The direction of entrepreneurship education should emphasize the impact of the entrepreneurship agenda in HEIs on the longterm effects of the learning process in producing and developing quality people to contribute to the development of the country